2021
DOI: 10.1016/j.ejvs.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Percutaneous Access Does Not Confer Superior Clinical Outcomes Over Cutdown Access for Endovascular Aneurysm Repair: Meta-Analysis and Trial Sequential Analysis of Randomised Controlled Trials

Abstract: WHAT THIS PAPER ADDSA meta-analysis was conducted of the most up to date, randomised clinical trial data of percutaneous vs. cutdown endovascular aneurysm repair (EVAR). The risk of bias was assessed with the updated Cochrane methodology, and the evidence was appraised with the GRADE system (Grades of Recommendation, Assessment, Development and Evaluation). Percutaneous EVAR was not found to have superior clinical outcomes to cutdown EVAR. The studies were judged to be high risk of bias or have some concerns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…EVAR does not aim to replace the aneurysmal sac, but excludes it from systemic circulation by minimally invasive implantation of a stent graft [ 270 ]. The stent graft is delivered to the abdominal aorta through the femoral artery, either by a percutaneous approach or by a surgical cut-down [ 271 ]. After confirmation of the exact vessel measurements by digital subtraction angiography, the delivery system is inserted over a stiff guidewire and then deployed and ballooned to expand and attach the stent graft to the aortic wall.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…EVAR does not aim to replace the aneurysmal sac, but excludes it from systemic circulation by minimally invasive implantation of a stent graft [ 270 ]. The stent graft is delivered to the abdominal aorta through the femoral artery, either by a percutaneous approach or by a surgical cut-down [ 271 ]. After confirmation of the exact vessel measurements by digital subtraction angiography, the delivery system is inserted over a stiff guidewire and then deployed and ballooned to expand and attach the stent graft to the aortic wall.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…The various types of endoleaks are the most common complication of EVAR and often require reintervention [ 277 ]. Other complications of EVAR include problems related to the access site, especially when the iliac arteries are small, calcified or severely tortuous [ 271 ], and a systemic inflammatory response termed ‘post-implantation syndrome’ in the early postoperative phase [ 278 ]. Complex endovascular aortic repair should only be advised at tertiary university hospitals, due to the necessary case numbers for experience in both complex EVAR and OSR, in case of complication management [ 273 , 274 ].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Stent migration (%) 0 (0.0) 0 (0.0) 2 (13.3) systematic reviews with meta-analyses of RCTs only, no significant difference in SSI incidence was seen [19,20]. In one of the reviews [20], a significant decrease in seroma/lymphorrhea incidence with PCD was demonstrated.…”
Section: Correctly Allocated N=28mentioning
confidence: 97%
“…As no previous studies reported PCOs, we used the incidence of access site complications to estimate the sample size of the SWEET trial. According to previous studies, the incidence of access site complications in percutaneous EVAR was 7.64%, compared with 11.81% in cutdown EVAR (13). We estimated the number of patients needed in this non-inferiority trial with noninferiority margin of 0.10 (bilateral α 5%, power 80%) by PASS 15.0 software, and 54 patients are required for percutaneous and cutdown EVAR group, respectively.…”
Section: Sample Sizementioning
confidence: 99%
“…In addition, no RCTs have been published comparing two types of access in TEVAR. Though the recent meta-analysis revealed comparable access complication rates between two access procedures, it is noteworthy that no studies reported patient-centered outcomes (PCOs), for instance, patient's experience and quality of life after surgery (13). Considering its relatively small impact on prognosis and large impact on quality of life, PCOs may be a new perspective to shed light on the selection of access procedures in EVAR or TEVAR.…”
Section: Introductionmentioning
confidence: 99%